2007
DOI: 10.1152/ajpregu.00304.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration-induced drinking decreases Fos expression in hypothalamic paraventricular neurons expressing vasopressin but not corticotropin-releasing hormone

Abstract: Wotus C, Arnhold MM, Engeland WC. Dehydration-induced drinking decreases Fos expression in hypothalamic paraventricular neurons expressing vasopressin but not corticotropin-releasing hormone. Am J Physiol Regul Integr Comp Physiol 292: R1349 -R1358, 2007. First published October 26, 2006; doi:10.1152/ajpregu.00304.2006 rats exhibit a rapid suppression of plasma corticosterone following drinking. The present study monitored Foslike immunoreactivity (Fos) to assess the effect of WR-induced drinking on the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…After just 1 hour, c‐Fos immunoreactivity disappeared in the majority of these neurons. A similarly rapid decrease in c‐Fos‐immunoreactivity has been observed in a group of dehydration‐activated neurons in the hypothalamus following an analogous sequence of water deprivation and brief access to water (Wotus et al,2007). The inactivation of HSD2 neurons after salt ingestion may be mediated by salt‐activated neurons in the surrounding NTS and AP, either directly or via inhibitory interneurons (see Sequeira et al,2006).…”
Section: Discussionmentioning
confidence: 53%
“…After just 1 hour, c‐Fos immunoreactivity disappeared in the majority of these neurons. A similarly rapid decrease in c‐Fos‐immunoreactivity has been observed in a group of dehydration‐activated neurons in the hypothalamus following an analogous sequence of water deprivation and brief access to water (Wotus et al,2007). The inactivation of HSD2 neurons after salt ingestion may be mediated by salt‐activated neurons in the surrounding NTS and AP, either directly or via inhibitory interneurons (see Sequeira et al,2006).…”
Section: Discussionmentioning
confidence: 53%
“…These two complementary PVN outputs act in concert at the level of the kidneys to properly modulate water and Na + reabsorption/excretion, restoring fluid and electrolyte homeostasis . Moreover, disturbances of fluid homeostasis also result in the activation of CRH neurones with the concomitant engagement of the hypothalamic‐pituitary‐adrenal axis , thus contributing to a multimodal homeostatic response to this type of physiological stressors. Although the general neuroanatomical, neurochemical and physiological features of these neurosecretory and sympathetic responses evoked during an osmotic/fluid challenge are well characterised , knowledge about how the activities of these distinct neuronal populations are coordinated, and whether this coordination results from local integrative processes within the PVN, is largely absent.…”
Section: The Pvn Of the Hypothalamus: An Ideal Model System For Studymentioning
confidence: 99%
“…Indeed, it was found (not bublished results) that the plasma level of the primary glucocorticoid (cortisol) in G. tarabuli was comparatively high (292±51 ng/ml), with the same essay method the plasma corticosterone levels in laboratory rat under basal conditions had been estimated to 28.8±7.9ng/ml [23]. In their interesting study Wotus et al, 2007 have shown a positive correlation between plasma levels of corticosterone and the hypothalamic hormone, vasopressin (AVP) in dehydrated rats [24]. This evidence may constitute another argument in favour of a potent steroidogenesis activity; bearing in mind that plasma AVP concentrations were higher in desert rodents than in laboratory rats, as was…”
Section: Discussionmentioning
confidence: 96%